2022
DOI: 10.1371/journal.pone.0267458
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers use of psychological support resources during COVID-19; a mixed methods approach utilising Pillar Integration Analysis

Abstract: Objectives We sought to examine healthcare workers (HCWs) utilisation of formal and informal psychological support resources in the workplace during the first and third waves of the COVID-19 pandemic in Ireland. Methods A convergent mixed methods approach was undertaken. Four hundred and thirty HCWs in the Mid West and South of Ireland responded to an online survey in terms of their use of psychological support resources during Wave 1 (April/May 2020) of COVID-19. Thirty-nine HCWs undertook in depth intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…On the other hand, the majority of participants (51.2%) do not know whether it is available or not, this could be attributed to what has been noticed by Gilleen et al 72 that healthcare workers may not appropriately prioritise their mental health, and existing formal support mechanisms require healthcare workers to initiate contact with the resource. This requires an individual to recognise and act on their potential need 73. Similarly, Xiang et al 74 reported that although some healthcare workers might need psychosocial support, they rarely seek help.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the majority of participants (51.2%) do not know whether it is available or not, this could be attributed to what has been noticed by Gilleen et al 72 that healthcare workers may not appropriately prioritise their mental health, and existing formal support mechanisms require healthcare workers to initiate contact with the resource. This requires an individual to recognise and act on their potential need 73. Similarly, Xiang et al 74 reported that although some healthcare workers might need psychosocial support, they rarely seek help.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to better understand these patterns of help‐seeking behaviour among HSCWs and to gain further insight into their preferences for drawing upon informal supports and peer networks and to better understand any perceived barriers in accessing formal support systems. Whether this preference is a product of perceived inadequacy of formal supports across sectors requires further investigation, as do other general help‐seeking patterns and formal support barriers (Richards et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 20 When asked about what they need from psychological support programs, HCWs placed high value on resources that help them build coping skills, 24 have diverse providers, 22 assist a range of employee types, 26 provide individualized services, 20–22 provide timely access to support, 22,23 are free and easy to access, 20,22 can link them to higher levels of mental health care, 27 and provide confidential services 20,23,25 . In addition, HCWs note that clarity in messaging around psychological resources available is critical, 20,22,25,26 especially with regard to whom programs are intended to benefit. 26 …”
mentioning
confidence: 99%
“…Healthcare workers report several barriers to using emotional support resources, such as limited availability of evening/weekend appointments 20 ; time to participate 21–23 ; stigma or reluctance to engage with psychological supports 18,20–25 ; belief that psychological supports are only for specific types of HCWs 26 ; uncertainty about the efficacy of psychological supports 25 ; or wanting to speak with an expert, such as a clinical psychologist, instead of utilizing lay supports. 20 When asked about what they need from psychological support programs, HCWs placed high value on resources that help them build coping skills, 24 have diverse providers, 22 assist a range of employee types, 26 provide individualized services, 20–22 provide timely access to support, 22,23 are free and easy to access, 20,22 can link them to higher levels of mental health care, 27 and provide confidential services 20,23,25 . In addition, HCWs note that clarity in messaging around psychological resources available is critical, 20,22,25,26 especially with regard to whom programs are intended to benefit.…”
mentioning
confidence: 99%
See 1 more Smart Citation